Pengaruh Motivasi Belajar dan Kemampuan Memecahkan Masalah terhadap Hasil Belajar Matematika Siswa Kelas V SD - Zahrika, Nazala Aprian; Yulianto, Sigit (Paedagogie, 2026)
This study aims to analyze the effect of learning motivation and problem-solving ability on the mathematics learning outcomes of fifth-grade students at SD N 2 Kutoharjo on multiplication material. The research method used in this study is a quantitative method with an ex post facto approach. The type of data in this study is primary data, namely data obtained directly from the field. Data were collected through a learning motivation questionnaire, a problem-solving ability test, and mathematics learning outcome scores on multiplication material. Data analysis was carried out through inferential analysis consisting of normality tests, linearity tests, and multicollinearity tests. Then it was continued with multiple regression analysis, followed by hypothesis testing through the T-test, simultaneous F-test, and coefficient of determination. The results of the study indicate that learning motivation does not have a significant effect on the mathematics learning outcomes of fifth-grade students at SD N Kutoharjo. Meanwhile, the problem-solving ability variable has a significant effect on the mathematics learning outcomes of fifth-grade students at SD N Kutoharjo.